Digital practices in primary school: is the pupil protagonist? - Francesco Fabbro; Alberto Agosti; Elaine Correa (Firenze University Press, 2017)
Much of the political, economic and theoretical emphasis on the use of digital technology in school tends to focus on the child's agency in the learning processes. In this respect several educational policies and also some influential theories in the field of educational technology seem to assume that the use of technology at school leads to a more informal and participated learning. This paper takes into account the results of a qualitative research conducted with students attending Italian primary schools and explores their perceptions, representations and positions concerning their experience with digital media in school. On the one hand, the paper highlights how students very often perceive digital technology as a useful and fun support of their learning process at school. On the other hand it presents and discusses some problems suggested by children concerning both their digital practices at school, as well as the different ways in which students represent themselves and their relationships in the classroom when they use digital media. The paper concludes with a summary of the research results followed by the proposal of a participated teaching design informed by a dialogue with the pupils.   Pratiche digitali nella scuola primaria: il bambino è protagonista? Buona parte dell'enfasi politica, economica e teorica sull'uso della tecnologia digitale a scuola è posta sull'agency del bambino nei processi di apprendimento. In questo senso diverse politiche educative e anche alcune influenti teorie elaborate nel campo delle Tecnologie dell'Educazione sembrano presupporre che l'impiego della tecnologia a scuola renda l'apprendimento più informale e partecipato. L'articolo si basa sui risultati di una ricerca qualitativa condotta con allievi frequentanti la scuola primaria allo scopo di esplorare le percezioni, le rappresentazioni e le posizioni dei bambini rispetto alla loro esperienza con i media digitali a scuola. Da un lato l'articolo mette in luce come gli allievi percepiscono in maniera piuttosto condivisa la tecnologia digitale come un utile e divertente supporto al loro apprendimento a scuola, dall'altro esso presenta e discute anche alcune criticità indicate dai bambini rispetto alle loro pratiche digitali in ambito scolastico, nonché come gli allievi rappresentano se stessi e le loro relazioni in classe quando usano i media digitali. L'articolo si conclude con una sintesi dei risultati della ricerca, seguita dalla proposta di una progettazione didattica partecipata e informata dal dialogo con i bambini.